Expand (2x-3)(4x+4) using the FOIL method.

  • Google+ icon
  • LinkedIn icon
  • 1244 views

Question: 

Expand (2x-3)(4x+4) 

We will be using the FOIL method. FOIL is an ancronym: 

F=first

O=outside

I=inside

L=last

So, to begin, we start with the first term in each bracket, and multiply them together. 

2x*4x=8x2

Next, we take the outside terms of the brackets, so 2x and 4.

2x*4=8x

Now, we move onto the inside terms. Now this may seem a little complicated. As the first bracket is (2x-3), we must always involve the fact that the 3 is negative. So, we are using the figures, -3 and 4x

-3*4x=-12x

Finally, the last terms 

-3*4=-12

We then add all these answers up

8x2+8x-12x-12=

8x2-4x-12

Therefore (2x-3)(4x+4)=8x2-4x-12

 

 

Miriam W. GCSE English Literature tutor, A Level English Literature t...

About the author

is an online GCSE Maths tutor with MyTutor studying at Edinburgh University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok